PENGARUH UMUR BETINA Drosophilla melanogaster strain tx TERHADAP JUMLAH ANAKAN DAN JENIS KELAMIN F1 SEBAGAI BAHAN PANDUAN PRAKTIKUM GENETIKA - Wijayanti, Antik Nur; Lukitasari, Marheny (Jurnal Florea, 2014)
Every living organism has the ability to reproduce that aims to maintain the kind ( species). Sexual maturity conditions of Drosophilla melanogaster will affect the outcome of the offspring ,that is a number of offspring and a kind offspring sex. Sexual maturation of female D. melanogaster individuals also greatly affect to the offspring conditions. Genetic research using D. melanogaster as an experimental material will be interesting and challenging for the university students . The purpose of this study was to determine: 1)The effect of age of female D. melanogaster strains tx on offspring number and the sex of F1. 2) The research results will use as a guide to the preparation of the genetics lab. The study was conducted using a completely randomized design methods . Data were analyzed using analysis of variance of the path (oneway Anova) followed further test by 5 % BNT test. Data showed the effect of age of female D. melanogaster strains tx on a number of offspring and the kind sex of F1 . The average number of offspring at various ages females are 149.38 . The average of are 72.03 and 77.34 of the female. After further testing with BNT in 5% of level indicates that the number of F1 offspring in females treatment aged 12 , 24 , 36 and 48 hours resulted in a lot of different number of offspring significantly with the number of female progeny from crosses age 60 , 72, 84 and 96 hours resulted in the number of little offspring. From the study it can be concluded that the age of the female D. melanogaster strains tx effect on a number of offspring and a kind of F1 sex of progeny . The older females ,the number of offsprings produced are less, because females decreased fertility and fecundity . Individual males have a higher mortality compared with all age female D. melanogaster strains tx . Keyword : Females Age , D. melanogaster strain Tx, Practical Guidelines .